Neovascularization: topical effects of streptococcus thermophilus and low level laser therapy in treatment of diabetic wound in rats - Kumari, Devi; Khan, Hina; Jiskani, Asad R.; Rafique, Muhammad; Asif, Muhammad; Kumar, Vijay; Maqsood, Syed (International Journal of Research in Medical Sciences, 2019)
Background: Diabetic wound is a major socioeconomic debilitating problem in this society. Various treatment options are available but still it requires better treatment option. In diabetes mellitus the oxygenation to the tissues is reduced. In this study effects of low level laser therapy were compared with topical application of Streptococcus thermophilus on diabetic wounds that induces formation of new blood vessel and free radical scavenging system, a comparative study to get better treatment option for diabetic wounds. Methods: 18 male rats were selected and divided randomly into three groups. Diabetes was induced in all the rats by using the Alloxan monohydrate at a dose of 120mg/kg of the body weight. Group A was treated with normal saline, group B was treated with low level laser therapy and group C was treated with Streptococcus thermophilus topically. Skin tissues were collected on day three and seven, slides were prepared for microscopic examination to observe the new blood vessels formation. Results: Mean number of new blood vessel formation was observed in group B compared with group A and C. Significant vasculogenesis was seen in group B when treated with Low level laser therapy. Conclusions: In the group of low level laser therapy new blood vessel formation was seen with better wound healing. It means LLLT provides better oxygenation to the tissues by generation of new blood vessels compared with Streptococcus thermophilus and normal saline.